Improved electrochemical performance of graphene oxide supported vanadomanganate (IV) nanohybrid electrode material for supercapacitors. Issue 3 (15th February 2020) - Kumari, Sparsha; Maity, Sukanya; Vannathan, Anjana A.; Shee, Debaprasad; Das, Partha Pratim; Mal, Sib Sankar
Abstract: Graphene oxide (GO)-supported polyoxometalates (POMs) have been considered as promising electrode materials for energy storage applications due to their ability to undergo fast and reversible redox reactions. Herein, vanadomanganate-GO composites (K7 Mn IV V13 O38 .18H2 O-GO with 2:1 and 4:1 ratio) were investigated for use as potential electrode materials in supercapacitors (SCs). The K7 Mn IV V13 O38 .18H2 O (MnV13 ) was synthesized and anchored on GO through electron transfer interaction and electrostatic interaction to make the composite electrodes for the present study. All synthesized electrode materials were fully characterized by various techniques, e.g., Fourier Transform Infrared (FTIR) Spectroscopy, Powder X-ray Diffraction (XRD), Scanning Electron Microscopy/Energy Dispersive X-ray Spectroscopy (SEM/EDS) and High Resolution-Transmission Electron Microscopy (HR-TEM). The electrochemical properties of MnV13 /GO composites with different MnV13 /GO ratios were investigated by two-electrode cyclic voltammetry (CV) and galvanostatic charge/discharge (GCD) in different electrolytes. The MnV13 /GO composite of ratio 2:1 in 1 M LiCl electrolyte and that of ratio 4:1 in 1 M Na2 SO4 electrolyte showed significant specific capacitance values of 269.15 F/g and 387.02 F/g, respectively and energy density of 37.38 Wh/kg and 53.75 Wh/kg, respectively for a scan rate of 5 mV/s. Interestingly, the 1:1 (MnV13 /GO) composite in 1 M Na2 SO4 and 1 M LiCl electrolytes showed very low specific capacitance values as the deposition of MnV13 on GO was not sufficient, as indicated by FTIR and SEM. Thus, it is evident that the specific capacitance value of these composite materials depends on the amount of MnV13 deposited on GO and these composite materials exhibit the potential to improve the performance of GO-based SCs.